A guide to programming logic and design : - Farrell, Joyce (Course Technology, 1999)
This title is a language-independent introduction to programming logic. It provides users with a structural approach to problem-solving in any language. Examples used in the book translate easily into modern languages such as C++, Pascal, Java, and Visual Basic.